A Comparative Study of Source Language Texts Used in the Indonesian Translations of Tao Te Ching - Budianto, Pauw (Bina Nusantara University, 2019)
This research aimed to show the Indonesian translation of Tao Te Ching that commonly did not state clearly the source text used as translation base, although some translations put Chinese source text in its translation book. This research tried to use a comparative method to analyze the differences of source texts used in two versions of Indonesian translations of Tao Te Ching, i.e., Lika and Wang, and its impact to translation products, then compared those source texts used with five original versions of Tao Te Ching as base texts references. The results show that (1) the differences between the two source texts occur mainly in four aspects: punctuation marks, pauses, characters, text redundant, and loss. (2) Source texts used by these two Indonesian versions are very close to the most widespread original versions; He Shanggong and WangBi commentary versions, with some changes in some places. Lika source text is quite close to HeShanggong version, Wang source text is quite close to the Wang Bi version. Some intentional changes in source text occur in Lika.